Bridging Tradition and Innovation: Transformative Educational Practices in Museums with AI and VR - Michele Domenico Todino; Eliza Pitri; Argyro Fella; Antonia Michaelidou; Lucia Campitiello; Francesca Placanica; Stefano Di Tore; Maurizio Sibilio (Computers, 2025)
This paper explores the intersection of folk art, museums, and education in the 20th century, with a focus on the concept of art as experience, emphasizing the role of museums as active, inclusive learning spaces. A collaboration between the University of Salerno and the University of Nicosia has developed virtual museum environments using virtual reality (VR) to enhance engagement with cultural heritage. These projects aim to make museums more accessible and interactive, with future potential in integrating artificial intelligence NPC and VR strategies for personalized visitor experiences of the Nicosia Folk Art Museum.